2018
DOI: 10.1101/431031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular mechanism for salt stress-induced microtubule array formation in Arabidopsis

Abstract: 44Microtubules are filamentous structures necessary for cell division, motility and morphology, 45 with dynamics critically regulated by microtubule-associated proteins (MAPs). We outline 46 the molecular mechanism by which the MAP, COMPANION OF CELLULOSE 47 SYNTHASE1 (CC1), controls microtubule bundling and dynamics to sustain plant growth 48 under salt stress. CC1 contains an intrinsically disordered N-terminus that links microtubules 49 at evenly distributed distances through four conserved hydrophobic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The CC proteins and more specifically the CC1 MT-binding domain are indispensable for the rearrangement of the CSC-MT machinery in response to salt stress (Endler et al , 2015;Kesten et al , 2018) . Consequently, mutants affected in CC function show stunted growth on salt containing media (Kesten et al , 2018) . Here, we show that the same CC1 domain is directly involved in the regulation of the CSC-MT machinery upon biotic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CC proteins and more specifically the CC1 MT-binding domain are indispensable for the rearrangement of the CSC-MT machinery in response to salt stress (Endler et al , 2015;Kesten et al , 2018) . Consequently, mutants affected in CC function show stunted growth on salt containing media (Kesten et al , 2018) . Here, we show that the same CC1 domain is directly involved in the regulation of the CSC-MT machinery upon biotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…This mutual support has been reported by several studies, especially under abiotic stress conditions such as drought and salt (Gutierrez et al , 2009;Nick, 2013;Endler et al , 2015;Wang et al , 2016) . Recently, CCs were shown to be indispensable for the recovery of the cortical MT array and CSC activity under salt stress (Endler et al , 2015) , and the microtubule interacting N-terminus of CC1 to be key for this function (Kesten et al , 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…4 We previously showed that AtTRAPPC11, and plausibly TRAPPIII, regulates SYP61-mediated post-Golgi trafficking. 4 Thus, it is tempting to speculate that defective trafficking of CESA6, BRI1, PIP1; and other PM residents critical the stress response, [19][20][21][22][23][24] evidenced by their abnormal intracellular accumulation, is responsible for the salt hypersensitivity of attrappc11.…”
mentioning
confidence: 99%